Accumulation of Mast Cells in the Lesions and Effects of Antiallergic Drugs on the Patients with Inflammatory Bowel Disease. (9th May 2013) - Kurosawa, Motohiro; Nagai, Hiroichi
Abstract : The pathomechanism of inflammatory bowel disease (IBD) has not yet been fully demonstrated. However, it is well known that mast cells are present in the gastrointestinal tract, suggesting that mast cells may take part in it. So, we investigated the number of mast cells in IBD, such as ulcerative colitis (UC) and eosinophilic colitis, and showed that the number of mast cells was increased in the inflammatory lesions. We also presented a case of UC which was treated successfully with an antiallergic drug, tranilast. Furthermore, possible new approaches to treating the disease with immunomodulators including suplatast are introduced. However, our investigations were performed with a limited number of patients with IBD, and additional further studies are required to confirm the findings.